Revisiting the Translator’s Visibility: Does Visibility Bring Rewards? - Liu, Fung-Ming (Meta, 2013)
There has been a huge revival of interest in the role of translators and their visibility. Some Translation Studies scholars have mobilized French sociologist Pierre Bourdieu’s theorical concepts of field, habitus and capital to carry out empirical research studies in an attempt to understand how translators or interpreters perceive their roles and what kind of capital they pursue. This article presents part of the findings from a large empirical study in which quantitative and qualitative approaches are combined in an attempt to carry out a thorough investigation of translators’ visibility, understood as the capacity to communicate directly with clients and/or end-users. The present article reports on the quantitative analysis of the relationship between translator’s visibility and the amount of capital that they say they receive. The analysis is based on 193 Chinese translators in China, Hong Kong, Taiwan and Macao. The findings suggest that visibility is rewarding in terms of social exchanges and learning experience, but not in terms of pay and prestige. In addition, the analysis shows that some social variables including sex, level of education, region that the translator lives in, the translator’s major field of study and the time spent on translation are not related to visibility or capital received. Meanwhile, the appearance of the translator’s name on translations is significantly related to the capital received.